On accelerating the convergence of the successive approximations method - Cătinaş, Emil (Rev. Anal. Numér. Théor. Approx., 2001)
In a previous paper of us, we have shown that no q-superlinear convergence to a fixed point \(x^*\) of a nonlinear mapping \(G\) may be attained by the successive approximations when \(G^′(x^*)\) has no eigenvalue equal to 0. However, high convergence orders may be attained if one considers perturbed successive approximations. We characterize the correction terms which must be added at each step in order to obtain convergence with q-order 2 of the resulted iterates.